Galaxy tense A+: the effectiveness of English tenses board game among tertiary students / Ainul Husna Ahmad Puad and Suzzana Othman - Ahmad Puad, Ainul Husna; Othman, Suzzana (Academy of Language Studies, 2023)
Learning through play is an excellent educational strategy for piquing students' interest in a certain subject. English tenses are undeniably one of the most crucial aspects of the English language. To compose a correct phrase or communicate anything to someone, one must convey the thoughts in the correct tenses. A lot of reading may not be sufficient to help students in improving their tenses skills. Therefore, this paper aims to find the effectiveness of an English tenses board game. This study adopts the quantitative approach, in which thirty (30) students from Universiti Teknologi Mara, Kampus Alor Gajah were selected as respondents to play the English tense board game. A before-game questionnaire, which includes a test, was provided to observe the level of English tenses they acquire. Moreover, an after-game questionnaire that also contains a test was employed to observe the improvement of the mistakes and errors made in the before-game questionnaire. The finding revealed that the board game helps to improve the students’ English tenses, which supports the idea of commercializing it into a wider market. Many of them answered correctly in the after-game test in comparison to the before-game test. This proves that they could learn effectively while playing the board game. In a nutshell, this study could also be an advantage to English teachers who intend to incorporate English tenses board games into their educational activity. Furthermore, these findings point to the relevance of interactive learning in driving language learners to expand their tenses skills.